Fertilizer and liming experiments with onions grown from sets - Tanaka, T.; Nishikawa, T.; Kawasaki, S. (Pesquisa Agropecuaria Brasileira, 2014)
The work discussed in this paper deals with the effects of liming, phosphorus fertilizer and micronutrients on the growth of onions from sets. The application of lime at the rate of 6 tons per hectare increased onion yields by 6.4 tons per hectare at Mogi das Cruzes and by 3.9 tons per hectare at Guatapará. Phosphorus fertilizer had a highly significant effect at both locations. The highest yield was obtained with a phophorus application of 372 kg of P per hectare at Mogi das Cruzes and 269 kg of P per hectare at Guatapará. At this location, micronutrients Zn, E and Mo provided a significant effect and when added to the fertilizer resulted in a yield increase of 90%.